Soluble CD147 regulates endostatin via its effects on the activities of MMP-9 and secreted proteasome 20S - Rahat, Maya M.; Sabtan, Hala; Simanovich, Elina; Haddad, Amir; Gazitt, Tal; Feld, Joy; Slobodin, Gleb; Kibari, Adi; Elias, Muna; Zisman, Devy; Rahat, Michal A. (Frontiers in Immunology, 2024)
During progression of rheumatoid arthritis (RA), angiogenesis provides oxygen and nutrients for the cells’ increased metabolic demands and number. To turn on angiogenesis, pro-angiogenic factors must outweigh anti-angiogenic factors. We have previously shown that CD147/extracellular matrix metalloproteinase inducer (EMMPRIN) can induce the expression of the pro-angiogenic factors vascular endothelial growth factor (VEGF) and matrix metallopeptidase 9 (MMP-9) in a co-culture of the human HT1080 fibrosarcoma and U937 monocytic-like cell lines. However, whether CD147 influences anti-angiogenic factors was not known. We now show that relative to single cultures, the co-culture of these cells not only enhanced pro-angiogenic factors but also decreased the anti-angiogenic factors endostatin and thrombospondin-1 (Tsp-1), generally increasing the angiogenic potential as measured by a wound assay. Using anti-CD147 antibody, CD147 small interfering RNA (siRNA), and recombinant CD147, we demonstrate that CD147 hormetically regulates the generation of endostatin but has no effect on Tsp-1. Since endostatin is cleaved from collagen XVIII (Col18A), we applied different protease inhibitors and established that MMP-9 and proteasome 20S, but not cathepsins, are responsible for endostatin generation. MMP-9 and proteasome 20S collaborate to synergistically enhance endostatin generation, and in a non-cellular system, CD147 enhanced MMP-9 activity and hormetically regulated proteasome 20S activity. Serum samples obtained from RA patients and healthy controls mostly corroborated these findings, indicating clinical relevance. Cumulatively, these findings suggest that secreted CD147 mediates a possibly allosteric effect on MMP-9 and proteasome 20S activities and can serve as a switch that turns angiogenesis on or off, depending on its ambient concentrations in the microenvironment.